Syngas biomethanation: Study of process performances at high syngas flow rate in pressurized stirred column. (May 2023) - Figueras, J.; Benbelkacem, H.; Dumas, C.; Buffiere, P.
Graphical abstract: Highlights: The performances of a syngas biomethanation process at high flow rate were studied. Syngas flow rate was gradually increased in a pressurized stirred column. High methane productivity and high H2 and CO conversion were achieved. A biological enhancement factor hypothetically enhances the mass transfer rate. Abstract: Syngas biomethanation is a promising technology for waste to energy conversion. However, it had not yet been tested at high syngas flow rates. The aim of this study was to assess the possibility for syngas biomethanation to reach high methane productivity at higher syngas inflow rate. A pressurized stirred column was implemented. The syngas inflow rate was gradually increased, and two different increase strategies were compared. The highest methane productivity achieved yet with syngas-biomethanation was obtained, with 23.2 LCH4 /L/d, with high conversion efficiencies of 89% for H2 and 82% for CO. The mass transfer performances of the process were investigated, and the existence of a biological enhancement factor was observed. Considering an enhancement factor in bioprocesses is a pioneering concept that could change the way we design bioreactor to improve mass transfer. The high methane productivity obtained in this study paves the way for the process industrialization.